2018
DOI: 10.3889/oamjms.2018.097
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiles in Obese Children and Adolescents with Insulin Resistance

Abstract: BACKGROUND:In the past several decades, the increasing frequency of overweight and obese children and adolescents in the world has become a public health problem. It has contributed significantly to the already high tide of diabetes, cardiovascular and cerebrovascular diseases.AIM:To investigate the frequency of insulin resistance and to evaluate the metabolic profile of insulin resistant and non-insulin resistant obese children and adolescents.SUBJECTS AND METHODS:The study included 96 (45 boys, 51 girls) obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 59 publications
3
20
0
5
Order By: Relevance
“…25 Kostovski et al has concluded that insulin resistant obese children and adolescents tend to have a worse metabolic profile in comparison to individuals without insulin resistance. 26 Above two studies support our finding.…”
Section: Discussionsupporting
confidence: 86%
“…25 Kostovski et al has concluded that insulin resistant obese children and adolescents tend to have a worse metabolic profile in comparison to individuals without insulin resistance. 26 Above two studies support our finding.…”
Section: Discussionsupporting
confidence: 86%
“…A similar result was found in a study in Jakarta (Pulungan et al, 2013). In contrast, A study by Kostovski in Macedonia showed that the percentage of female experienced insulin resistance was higher than the male with p = 0.009 (p <0.05) (Kostovski et al, 2018). The explanation to this finding was because 52.94% of the female were in adolescence while 68.89% the male was in the pre-adolescent age.…”
Section: Discussionsupporting
confidence: 83%
“…However, the effect of the mentioned factors on the preoperative serum glucose level is still in debate [ 9 ]. Age and body weight of children are considered important factors that influence serum glucose levels [ 10 ]. Children with lower body weight are more susceptible to hypoglycemia during fasting compared to children with higher body weight [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%